An Analysis of Language Function and Language Expression Used by Guest Service Agent at Hotel Puri Saron Lovina Baruna Beach Cottages - Suardika, Kadek Deki (STKIP AGAMA HINDU SINGARAJA, 2024)
This study aims to analyze several problems specifically focusing on the language functions and expressions utilized by Guest Service Agents at the Puri Saron Lovina Hotel. Employing a descriptive qualitative approach, the research involves five receptionists who meet the established criteria for participation. Data collection follows a series of steps, beginning with observations, and progressing to interviews, which are recorded for accuracy using audio equipment. The collected data is then systematically examined, with particular attention paid to analyzing grammar. The study identifies eight key language functions and expressions used by the five receptionists, including , 1) Asking for Opinion, 2) Giving Opinion, 3), Asking for Directions, 4) Giving Directions, 5) Agreement, 6) Disagreement, 7) Complaint, 8) Greeting. This chapter has provided a comprehensive overview of the language functions and expressions employed by Front Office Staff, particularly Guest Service Agents and Receptionists, at Hotel Puri Saron Lovina Baruna Beach Cottages. Through systematic observation and interviews, we identified a range of language functions critical for effective communication in the hospitality context.